Pollutions marines et lutte à terre - Vincent Herbert (Territoire en Mouvement)
With the local scale, the actors of the territory often perceive risks of coastal pollution by hydrocarbons by a maritime entry, where the preventive solutions would emanate systematically from the international legal authorities (IMO and various conventions, EU and the packages “Erika I and II”...). This continental perception is due, partly, with the ambiguity of the lake of definitions of the coastline, between the terrestrial limit and the marine limit. Nevertheless, within the framework of the coastal management of pollution, it is advisable to distinguish the maritime risk from the coastal risk. In this context, the risk of coastal pollution by hydrocarbon must be interpreted like an emanating risk of the risk related to the maritime transport. The identification of the coastal vulnerability, which integrates social impact strength, must facilitate a better response in the field of the coastal fight.